Impact of Famine of 1924—1925 on Social and Political Mood of Peasantry in Tambov Province - V. A. Ippolitov (Научный диалог)
The causes and consequences of the famine in the Tambov province in 1924—1925 are examined in the article. The relevance of the study is due to the need for a comprehensive study of the Russian peasantry of the “revolutionary breakthrough generation” (born at the turn of the 19th and 20th centuries). The main attention is paid to the impact of famine on the social and political moods of the peasantry. In order to determine the factors that influenced the self-awareness of the villagers, the documents of the funds of the Russian Archive of Social and Political History and the State Archive of Social and Political History of the Tambov Region were studied. A wide range of documents of central and local party organizations and state security bodies are used in the article. The social practices resorted to by rural society for survival in extreme crop failure conditions are considered. Relations between the main social groups of the village are analyzed. Special attention is paid to the mechanisms of state aid to the starving. As a result of the conducted research, an increase in oppositional attitudes among the peasantry has been proven. An increase in religiosity and egalitarian tendencies in rural areas is considered characteristic. It was established that significant state aid contributed to the spread of peasant loyalty to the government.